2019
DOI: 10.1016/j.rmed.2019.06.021
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of relationships between native and inhalation device specific spirometric parameters as a step towards patient tailored inhalation device selection

Abstract: ResultsMore than 60% of the patients stated that their current device is the easiest to use. The means of the measured PIFdev values were 91.4 L/min, 77.1 L/min and 77.5 L/min for Breezhaler ® , Genuair ® , and Turbuhaler ® , respectively. PIFdev were significantly higher for males than for females, but differences upon age, BMI and disease severity group were not significant (at p=0.05). Peak inspiratory flows through the inhalers (PIFdev) correlated best with their native spirometric counterparts (PIF) and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 23 publications
0
30
0
Order By: Relevance
“…In a few studies, instructions were in line with patient information leaflets/Instructions for Use brochures. 7,51,53,56,59,62,68,71,72,74 In other studies, the instructions were not consistent with the Instructions for Use leaflet for the DPI being evaluated. 76,79 The contents of the Instructions for Use of the In-Check™ DIAL were consistent with instructions provided to patients using DPIs in one study 58 but not in others.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…In a few studies, instructions were in line with patient information leaflets/Instructions for Use brochures. 7,51,53,56,59,62,68,71,72,74 In other studies, the instructions were not consistent with the Instructions for Use leaflet for the DPI being evaluated. 76,79 The contents of the Instructions for Use of the In-Check™ DIAL were consistent with instructions provided to patients using DPIs in one study 58 but not in others.…”
Section: Discussionmentioning
confidence: 91%
“…Overall, the PIF measurement details, including inhalation instructions, were provided or participants were referred to patient information leaflets in 35 of the 47 studies (74.5%; Supplementary Table 1). 7,12,[21][22][23]26,[32][33][34]48,[51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66]68,[70][71][72][74][75][76]78,79 Instructions for exhalation before the inhalation maneuver were provided in 14 (29.8%) studies and included "exhale gently to FRC," 12,26,60,66 "complete exhalation," 21,23,57,74 "exhale to RV," 60,75 "deeply A gentle tap will dislodge the magnetic resetting weight, which will return the red cursor to a start position. When this has happened, the meter must turn through 180 degrees to return the magnetic weight to its resting positio...…”
Section: Pif In Published Studiesmentioning
confidence: 99%
“…More details on data charting for all of the papers included in the systematic scoping review can be found in Supplementary Table S4. [11,17,21,22,25,28,30,32,34,3 5,44,47] Age ↑; PIF ↓ 1 (r ranging from −0.19 to −0.84; odds ratio ranging from 1.05 to 1.07) 5/17 (29%) [18,19,29,36,46] Gender 14/35 10/14 (71%) [16][17][18][19]22,26,32,35,36,47] Female gender; PIF ↓ 2 (odds ratio ranging from 0.28 to 2.41)…”
Section: Association Of Pif With Patient or Disease Characteristicsmentioning
confidence: 99%
“…4/14 (29%) [11,21,29,34] Height 11/35 8/11 (73%) [16][17][18][19]22,28,32,44] Height ↓; PIF ↓ 3 (r ranging from 0.26 to 0.44) 3/11 (27%) [11,25,35] Age ↑; PIF ↓ 1 (r ranging from −0.19 to −0.84; odds ratio ranging from 1.05 to 1.07) 5/17 (29%) [18,19,29,36,46] discussed or controlled for, thus scoring negatively.…”
Section: Association Of Pif With Patient or Disease Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation